Theoretical Investigation of the Charge Transport Properties of the DPTTA p-Type Single Crystal to the Ambipolar DPTTA-F4TCNQ Cocrystal - Ding, Zhelin; Mu, Qiqi; Ren, Junle; Li, Yuyao; Shen, Qiguang; Zhang, Li; Zhang, Shoufeng (Journal of Basic & Applied Sciences, 2023)
Our research has been conducted on the charge transport properties of the single-crystal DPTTA and the cocrystal DPTTA-F4TCNQ using the density functional theory coupled with incoherent charge-hopping model. Charge mobility is primarily considered from the combination of reorganization energy and charge transfer integral, which are important parameters in model of the charge-hopping model. The reorganization energy of DPTTA in both single-crystal and cocrystal forms exhibits similar values. Consistent with the properties of super-exchange coupling and direct coupling when under the same type of coupling mechanism, it decreases with increasing distance from the core molecule. We conclude this section by using kinetic Monte Carlo combined with Einstein’s equation to derive the charge mobility, and find it to be consistent with the theoretical analysis. In our study, we propose corresponding theoretical guidelines for the rational realization of the ambipolarity of D-A complexes, hoping to contribute to the understanding and rational design of the basic mechanism of D-A complexes.